Sensitivity of the Elecsys Nucleocapsid Assay for the Detection of Preceding SARS-CoV-2 Infections. (26th July 2022) - Grunau, Brian; Tom, Janessa; Asamoah-Boaheng, Michael; O'Brien, Sheila F; Drews, Steven J; Sediqi, Sadaf; Lavoie, Pascal M; Barakauskas, Vilte; Goldfarb, David M
Abstract: Nucleocapsid serological assay sensitivity to identify severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infections among vaccinees and for Omicron cases is unclear. In this prospective study, the Elecsys nucleocapsid assay was 89% sensitive in identifying SARS-CoV-2 infections 14–607 days pre–blood collection. Sensitivity was similar when comparing by vaccination status, and in Omicron (vs pre-Omicron) cases.